Efektivitas SNEDDS Ekstrak Kulit Manggis Terhadap Bakteri P. mirabilis dan S. epidermidis yang Terdapat pada Ulkus Diabetik - Sari, Rafika; Pratiwi, Liza; Apridamayanti, Pratiwi (UI Scholars Hub, 2016)
Mangosteen rind possesses the ability to conduct antibacterial activity. Under the development relating to drug delivery system, SNEDDS were known to boost the penetration of active compound. The aim of this research is to compare the effectiveness of the antibacterial activity at both SNEDDS preparation and the ethanol extract of mangosteen rind as the antibacteria against the bacteria that cause diabetic ulcers with the most prevalence whether it was Gram positive or Gram negative bacteria like Proteus mirabilis and Staphylococcus epidermidis. The research started by maceration process with the crude extract as the result continued with the phytochemical screening which subsequently prepared as SNEDDS preparations. The SNEDDS preparation prepared earlier were then analyzed to see the content of the active compound using spectrophotometer UV-Vis and the measuring of antibacteria activity with bacteria growth inhibitory parameter at ethanol extract SNEDDS preparations of mangosteen rind then compared to ciprofloxacin and were analyzed the data afterwards using ANOVA. The results shows that SNEDDS preparation of mangosteen extract have an activity against both typed of bacteria that cause diabetic ulcers shows by significant differences between both group which is P.mirabilis bacteria group and S.epidermidis bacteria group in ANOVA test with significant number of 0,000 and shows significant differences between both group.